Decision-making factors in prenatal testing: A systematic review. Issue 1 (January 2021) - Di Mattei, Valentina; Ferrari, Federica; Perego, Gaia; Tobia, Valentina; Mauro, Fabio; Candiani, Massimo
This review examines the factors that affect the decision-making process of parental couples evaluating prenatal screening and diagnostic tests. A systematic search was performed using PubMed and PsycInfo databases. The 46 included studies had to: investigate the decision-making process about prenatal testing; focus on tests detecting trisomy 21, 18, 13, and abnormalities of sex chromosomes; be published in English peer-reviewed journals. The decision-making process seems composed of different levels: an individual level with demographic, clinical, and psychological aspects; a contextual level related to the technical features of the test and the information received; a relational level involving family and society.